Implementing of SSM Model: An Effort to Monitor the Learning Process at Home - Nasrum, Akbar; Marniati; Andi Tenri Sumpala (LPPM Undiksha, 2025)
Many mathematics learning models have been implemented in schools, but no learning model is specifically used to monitor the learning process at home. The purpose of this research is to create a learning model that can be used to monitor the learning process at home as well as serve as additional learning for students. The learning model developed is Structured, Systematic and Massive (SSM). Data collection used several questionnaires, namely content validation questionnaires (materials and quizzes), media validation questionnaires, test instruments and student response questionnaires. The data obtained were analyzed quantitatively and then described. The development of this model uses the Moodle LMS tool. This type of research is development research using the ADDIE model. The results showed that the developed model effectively monitored students’ learning process at home. In addition, the Criteria for Achieving Learning Objectives (KKTP) became easier after applying this model. The creation of this model is one of the alternative models for improving the quality of learning in schools. In conclusion, the Soft Systems Methodology (SSM) approach effectively understands and maps complex issues in home learning monitoring.